The Role of the Speech-Language Pathologist in the Schools for the Treatment of Voice Disorders: Working within the Framework of the Individuals with Disabilities Education Improvement Act - Ruddy, Bari Hoffman; Lewis, Vicki; Sapienza, Christine M. (Seminars in Speech and Language, 2013)
The role of the speech-language pathologist (SLP) has developed considerably over the past 20 years given the medical and technological advances in life-sustaining procedures. Children born with congenital, surgical, or “medically fragile” conditions become mainstreamed into regular school-based settings, thus extending the traditional role of the treating SLP and multidisciplinary team. Understanding the impact of associated voice disorders on educational performance requires dissemination of additional and important information, as eligibility decisions for students in school-based settings must be made within the framework of the federal legislation and regulations governing the provision of services for students with disabilities. This article discusses how to identify children with voice disorders under the Individuals with Disabilities Education Improvement Act (IDEA), the role of the SLP in various triaging scenarios, and how models of voice therapy can be integrated in a school-based setting.
Keywords: Child; student; voice disorder; IDEA; treatment; education